Cuidados de enfermería en niños con trastornos del espectro autista. - Cahuana Tixi, Yajaira Vanessa (2024)
Autism spectrum disorder (ASD) in children represents a significant challenge in providing nursing care due to its complexity and their particular needs. Despite the advances in understanding ASD in this population, gaps remain. The methodology used for this search consists of a bibliographic review that is documentary, descriptive, and comprehensive. Information was gathered from national and international health scientific databases, including Google Scholar, Scopus, ProQuest, Redalyc, SciELO, and university digital repositories. Also, other websites, such as the World Health Organization (WHO), American Psychiatric Association (APA), and Ecuador's Ministry of Public Health (MSP), were accessed. This research highlights the role of education and counseling provided by nursing professionals at all stages of ASD, from diagnosis to follow-up, becoming a crucial support for families. Various barriers and challenges in care provision were identified, including lack of knowledge about the disorder, deficiency of adequate protocols and guidelines, poor coordination between the health providers and the family, difficulties in establishing a therapeutic alliance, inadequate adaptation of the health strategies about each patient's limitations y social prejudices. The lack of professional training directly impacts the quality of care, limiting the ability of nurses to provide comprehensive attention. This research reveals a significant shortage of recent studies addressing this disorder, especially in the field of nursing at a global level, hindering an adequate understanding of the scope of ASD in the region.